Introduction: Frontline delivery of welfare‐to‐work in different European contexts. (30th October 2018) - van Berkel, Rik; Larsen, Flemming; Caswell, Dorte
Abstract: This themed issue contributes to European research on the role of front‐line work in the implementation of welfare‐to‐work policies. A number of factors underline the relevance of such study. First, the focus on activating and disciplining the unemployed seen in many countries may on the surface look similar. However, a closer look at these policies and how they unfold in different contexts reveals many and interesting differences. While all contain a certain level of disciplining and coercive elements, they also to a varying degree contain elements that focus on the upgrading of skills, building human capital and providing other types of support in promoting labour‐market participation. In turn, these policies contain both people processing and people changing technologies that are used for different aspects of policy delivery. In addition, policy developments have gradually expanded the client group of these policies, including more hard‐to‐place unemployed, thus making the client group more heterogeneous. Finally, we have seen a strong political belief in the positive effects of using punitive sanctions. Research supports this belief when it comes to clients with high employability and limited problems besides unemployment, but the knowledge‐base is rather shaky when it comes to the hard‐to‐place clients with substantial problems. Using punitive sanctions or other disciplining or coercive measures in frontline work has caused controversy and resistance. In order to qualify our understanding of welfare‐to‐work policies, we need to take a step closer to where these policies are translated into reality for the target group.